Eva Apostolou and Charles Doyen (eds), Obolos 10. Coins in the Peloponnese. La monnaie dans le Péloponnèse. Proceedings of the Sixth Scientific Meeting of the Friends of the Numismatic Museum, Argos, May 26–29, 2011.: Volume 1: Ancient Times. Volume 2: Byzantine and Modern Times. - Grandjean, Catherine (Journal of Greek Archaeology, 2022)
Eva Apostolou and Charles Doyen (eds), Obolos 10. Coins in the Peloponnese. La monnaie dans le Péloponnèse. Proceedings of the Sixth Scientific Meeting of the Friends of the Numismatic Museum, Argos, May 26–29, 2011. Volume 1: Ancient Times. Volume 2: Byzantine and Modern Times. BCH Supplément 57. pp. 527 + 285, with figs, ills, maps. Athens: École Française d’Athènes, 2017. ISBN 978-2-86958-279-8, paperback €90.